Odour-mediated long-range avoidance of interspecific competition by a solitary endoparasitoid : a time-saving foraging strategy - Tamò, Cristina; Roelfstra, Lise-Lore; Guillaume, Suzanne; Turlings, Ted (My University, 2006)
1. In studies on optimal foraging strategies, long-range decisions in the pursuit of resource are rarely considered. This is also the case for sympatric parasitoids, which may be confronted with the decision to accept or reject host larvae that are already parasitized by a competing species. They can be expected to reject already parasitized hosts if it is likely that they will lose the resulting intrinsic competition. However, examples of such interspecific host discrimination are rare.
2. We propose that parasitoids that are not egg-limited should reject inferior hosts only if it saves them time, and that this will be achieved mainly when the parasitoids are able to detect competitors from a distance. We tested this hypothesis using the sympatric parasitoids Cotesia marginiventris (Cresson) and Campoletis sonorensis (Cameron).
3.C. sonorensis was found to be the superior intrinsic competitor but, upon contact with a host larva, both wasps readily accepted hosts that had already been parasitized by the other species. However, in an olfactometer experiment, C. marginiventris females were found to strongly avoid the odour of their superior competitor.
4. These results are in accordance with a time optimization scenario, whereby the inferior competitor accepts competition if it costs only an egg, but avoids competition if it may save time that can be allocated to the search for more profitable hosts.
5. Models on host discrimination strategies in parasitoids had not yet considered discrimination from a distance. Long-range foraging decisions can also be expected for other organisms that have to choose between resources of varying suitability and profitability.
Keywords: competition; host discrimination; olfaction; optimal foraging; parasitoids